KAJIAN YURIDIS PEMBATALAN AKTA PENGIKATAN JUAL BELI (PJB) TANAH YANG DIBUAT DIHADAPAN NOTARIS - T.BASWEDAN T. BASWEDAN (PREMISE LAW JURNAL, 2014)
ABSTRACT Land trading deed made before a public notary in a conditional agreement to bind the parties who have made the agreement in order to implement the main agreement which is the trading deed made before PPAT (Official Empowered to Draw up Land Deeds). This research was judicial normative. The factors which caused the cancellation of land trading deed was the agreement of the parties because the requirements of cancellation as it is stipilated in the clause of purchase agreement hass been fulfilled. The legal consequences of the cancellation of the land trading deed made before a public notary was compensation, cancellation of agreement, and cancellation with compensation. The legal complaint can be brought to the Court (litigation) afterthe warning (somatie) has been filed by the party that is harmed to the party that has cancelled it or those have breeched the land trading deed. Keywords: Cancellation, Land Trading Agreement, Notary